(untitled) (TAMADDUN NURI JURNALI, 2024)
Although the processes of trade relations that passed through the Northern branch of the Great Silk Road in the late 10th - early 11th centuries have been relatively widely studied, but the cities that have a great influence in these trade processes, Information about caravan centers and trade routes was not summarized and a single conclusion was reached. In the history of Khorezm, the issue of trade centers and trade routes during the Ma’muni dynasty is considered one of the most urgent problems, and this article is devoted to this topic.